Chronic Corynebacterium striatum Septic Arthritis in a Patient Referred for Total Knee Arthroplasty - Katharine Hollnagel; Jacob Willen; Michael Ellis; Yalda Soleimanifard; Robert Booth; Sumon Nandi (Case Reports in Orthopedics)
Background. While Corynebacterium striatum and other Corynebacterium species were historically considered contaminants, they are recently being identified as pathogens with increasing frequency. Case Summary. We report the case of a 78-year-old gentleman with a three-year history of knee pain and established diagnosis of osteoarthritis referred for consideration for total knee arthroplasty. He had no knee pain with passive range-of-motion. Plain films demonstrated bony erosions atypical for osteoarthritis. Joint aspiration white blood cell count was 30,548/mm3, but multiple cultures were positive for C. striatum. The infection was successfully treated with open irrigation and debridement, complete synovectomy, and six weeks of intravenous daptomycin. Conclusion. To our knowledge, this is the first report of chronic C. striatum septic arthritis of a native joint and only the third case of C. striatum septic arthritis of the knee.